DISTORSI TEOLOGI MISI KAUM OIKUMENIKAL INDONESIA DITINJAU DARI PENGAJARAN KISAH PARA RASUL 17:16-31 - James Damping (STT BIBLIKA JAKARTA, 2022)
This study aims to examine Acts 17:16-31 to find the principles of mission theology that are useful for providing the pillars of understanding in carrying out mission activities, so that they can be carried out correctly according to the will of God, the giver of the mission. It should be understood that theology and mission cannot be separated, because they are closely related. The relationship between these two fields is basically the essence of theology itself as a scientific discipline that contains two sides of understanding, namely theology is teaching about God and theology must lead people to God. Today's reality indicates that there are distortions in the understanding of some Indonesian ecumenical theologians. The distortions in question are related to the core meaning of mission news, the purpose of dialogue pluralism and the use of the christocentric method in mission activities. Paul's ministry in Athens as documented in Acts 17:16-31 teaches several important principles in carrying out cross-cultural missions, which are useful in helping missionaries analyze problems in the field and respond appropriately to them